Analytical Modeling of Filling Times for Metal Hydride–Hydrogen Storage Tanks With and Without Heat Reaction Recovery - Fatma Bouzgarrou; Sofiene Mellouli; Abdullah A. Faqihi (Energies)
The analysis of metal hydride (MH) tanks requires numerical modeling, which can be complemented by analytical studies. These analytical studies are valuable for swiftly sizing efficient reservoirs intended for hydrogen or thermal energy storage systems. This study aims to develop an analytical model for estimating the filling time of various metal hydride–hydrogen storage tanks under two conditions, with and without heat reaction recovery, utilizing phase change material (PCM). Four scenarios of the metal hydride tank are considered: (i) one with an external electrical drum heater, (ii) one with an external heat transfer fluid, (iii) one with a PCM jacket, and (iv) one with a sandwiched MH-PCM configuration. Furthermore, this study investigates the influence of the MH tank design, geometric parameters (dimensions, geometry), and operational conditions (pressure and temperature) on the filling time. Overall, this investigation offers a basis for calculating the filling times of various metal hydride–hydrogen storage tank types, enabling well-informed design and system optimization decisions.